Pemahaman dan Amalan Identiti Korporat dalam Kalangan Agensi Kerajaan di Negeri Kedah - Azlinda, Boheran Nudin (2011)
The need for corporate identity in the private and public organizations has become a debatable topic in many conversations. This has led many organizations to diversify their corporate identity to look more attractive and acceptable to the public. Therefore, this study is conducted to examine the understanding, development and corporate identity practices among government agencies in Kedah. A total of seven government agencies committed as respondents of the study and every agency is represented by an officer nominated by the agency. Research using qualitative method allow researchers to conduct face to face interviews with respondents. The data obtained were analyzed and titled to the specific elements using NVivo qualitative data analysis software version 8. The data analysis showed that the understanding of the corporate identity of government agencies are not much different than the understanding of western scholars associated with corporate identity. Through this study, new corporate identity formation elements were found which has not yet been discuss by the western scholar. The corporate identity practice showed that the approach used by Kedah government agency was different from the research done by western scholar. Thus this study shows that the Kedah state government agencies have the understanding, formation, and practice of corporate identity that is quite similar to the opinion of Western scholars.